Genetic variants in CYP7A1 and risk of myocardial infarction and symptomatic gallstone disease. (23rd February 2018) - Qayyum, Faiza; Lauridsen, Bo K; Frikke-Schmidt, Ruth; Kofoed, Klaus F; Nordestgaard, Børge G; Tybjærg-Hansen, Anne
Abstract: Aims: Myocardial infarction (MI) and gallstone disease (GSD) are intrinsically linked via cholesterol metabolism. We tested the hypothesis that genetic variants in the gene encoding cholesterol 7 alpha-hydroxylase (CYP7A1), the rate-limiting enzyme in the conversion of cholesterol to bile acids in the liver, are associated with risk of MI and GSD in the general population. Methods and results: We performed tests of association between lipid levels and eight rare non-synonymous mutations and two common variants, rs2081687 and rs3808607, in CYP7A1 in 100 149 individuals from the general population. We further tested whether weighted allele scores for rs2081687 and rs3808607, which were associated with increased plasma levels of low-density lipoprotein (LDL) cholesterol, were associated with an increased risk of both MI and symptomatic GSD. During a mean follow-up of 7 years (0–23 years), MI developed in 2326 individuals and GSD in 2007. For rare mutations, CYP7A1 allele count was associated with an increase in LDL cholesterol of 12% (0.4 mmol/L) for individuals with the highest vs. the lowest allele count ( P for trend = 3 × 10 −4 ). For common variants, CYP7A1 weighted allele scores in individuals with a score >0.04 vs. ≤0 were associated with stepwise increases in LDL cholesterol of up to 2.4% (0.08 mmol/L), and with corresponding multifactorially adjusted hazard ratios of 1.25 [95% confidence interval (CI) 1.10–1.41] for MI and 1.39 (95% CI 1.22–1.59) for GSD ( P for trend = 5 × 10 −4 and 2 × 10 −7, respectively). Results were similar in meta-analyses including publicly available data from large consortia. Conclusion: Genetic variants in CYP7A1 which are associated with increased levels of LDL cholesterol, are associated with an increased risk of both MI and GSD.